2012
DOI: 10.1603/ec11179
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Mulch and Acibenzolar-<I>S</I>-methyl Treatments Relative to Thrips (Thysanoptera: Thripidae) and Tomato Spotted Wilt Virus Incidence in Tomato

Abstract: Management of thrips-transmitted tomato spotted wilt (TSW) virus typically relies on tactics that either reduce the thrips vector numbers or change the plant's response to the virus to reduce economic loss. We attempted to quantify the interaction between two such tactics, reflective mulch and the plant activator acibenzolar-S-methyl (Actigard), respectively, on a TSW-susceptible tomato hybrid. A split plot experiment was conducted in 2009 and 2010 where main-plots were three types of plastic mulch (two metali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The light reßected by UV-reßective mulches disrupts this natural mechanism, thereby reducing the numbers of thrips landing on plants (Stavisky et al 2002, Momol et al 2004, Riley and Pappu 2004. In addition to disrupting host Þnding by thrips and other insects, UV-reßective mulch decreases incidence of insect-vectored diseases, including tomato spotted wilt, and increases yields (Greenough et al 1990, Stavisky et al 2002, Greer and Dole 2003, Hutton and Handley 2007, Diaz-Perez 2010, Riley et al 2012. Reitz et al (2003) reported that populations of O. insidiosus were reduced by UV-reßective mulches, thereby resulting in effects on predatorÐprey dynamics.…”
mentioning
confidence: 99%
“…The light reßected by UV-reßective mulches disrupts this natural mechanism, thereby reducing the numbers of thrips landing on plants (Stavisky et al 2002, Momol et al 2004, Riley and Pappu 2004. In addition to disrupting host Þnding by thrips and other insects, UV-reßective mulch decreases incidence of insect-vectored diseases, including tomato spotted wilt, and increases yields (Greenough et al 1990, Stavisky et al 2002, Greer and Dole 2003, Hutton and Handley 2007, Diaz-Perez 2010, Riley et al 2012. Reitz et al (2003) reported that populations of O. insidiosus were reduced by UV-reßective mulches, thereby resulting in effects on predatorÐprey dynamics.…”
mentioning
confidence: 99%
“…Metalized plastic mulch showed a lower incidence of TSWV in tomatoes than the plants grown on black plastic mulch [ 38 , 39 ]. A different study on silver and other colored plastic mulches on disease incidence indicates their effectiveness in thrips reduction, lowering or delaying the occurrence of tospovirus, and increased yield [ 28 , 40 , 41 , 42 , 43 , 44 ]. The objective of the present study was to determine the effectiveness of different polyethylene mulches (‘silver on black’, ‘silver on white’, ‘black on black’, ‘white on black’) and biorational insecticides such as Aza-direct ® (azadirachtin), Entrust ® SC (Spinosad), Grandevo ( Chromobacterium subtsugae strain PRAA4-1 T ), and Spear ® T (GS-omega/kappa-Hxtx-Hv1a) on thrips abundance, TCSV incidence, marketable yield and the volume of fruit production of tomato in South Florida.…”
Section: Introductionmentioning
confidence: 99%